Is stress related to itch in German students? Results of an online survey - Stephanie Kiupel; Jörg Kupfer; Sophia Kottlors; Uwe Gieler; Uwe Gieler; Gil Yosipovitch; Christina Schut (Frontiers in Medicine, 2023)
IntroductionGerman students report to be more stressed than the general population. Highly stressed students from other countries (United States, Australia, Saudi-Arabia) were found to have more skin symptoms, including itch, than lowly stressed students. The current study aimed to assess whether itch is associated with stress in a larger sample of German students.Methods838 students (3.2% of all invited students) took part in the questionnaire based study and filled in the Perceived Stress Questionnaire as well as a modified version of the Self-Reported Skin Questionnaire. Students were categorized into highly (HSS) and lowly stressed students (LSS) by determination of the 25th and 75th percentile.ResultsItch occurred significantly more often in HSS compared to LSS (OR = 3.41 (2.17–5.35)). In addition, itch intensity was significantly related to perceived stress.DiscussionThese findings not only highlight the importance of offering stress management trainings also to students in Germany in order to minimize itch, but also encourage future research on stress and itch in certain student subgroups.